Kumar's a treatise on insurance laws. - Gyanendra Kumar, 1910-; India (Allahabad : Law Publishers (India), 2006)
Revision of hand book on insurance laws with reference to India.
Subtitle: With Insurance Act, 1938; Insurance Rules, 1939;Insurance Regulatory and Development Authority Act, 1999; IRDA Regulations, 2000 under IRDA Act, 1999; General Insurance (Emergency Provisions) Act with scheme, 2000; Arbitration and Conciliation Act, 1996; Deposit Insurance and Credit Guarantee Corporation Act, 1961; Life InsuranceCorporation Act, 1956; Marine Insurance Act, 1963; Negotiable Instruments Act, 1881; Personal Injuries (Compensation Insurance) Act, 1963; Public Liability Insurance Rules, 1991; War Injuries (Compensation Insurance) Act, 1943; Insurance Ombudsman Redressal of Public Grievances Rules, 1998 alongwith allied acts.
Includes bibliographical references and index.
Keywords: Insurance law -- India